Why so unfit?: Assessing potential barriers to exercise adoption in middle-aged men - Towers AJ; Flett RA; Seebeck RF (The Author(s))
Compared to women, men:  have a higher mortality rate  consistently die younger  are more susceptible to sedentary-lifestyle related diseases (e.g., cardiovascular disease)  are more likely to engage in behaviours that increase risk of injury, disease, or death  are less likely to seek help with physical health. Despite these statistics, the amount of literature devoted to women’s health in the past two decades still greatly exceeds that devoted to men’s health. The result is that we actually know very little about what influences men’s health behaviours. Introduction We utilised the transtheoretical model of exercise behaviour change to determine the pattern of exercise adoption in middle-aged men. We also analysed whether this pattern was influenced by three potential barriers to exercise: poor self-rated health, low levels of internal health locus of control, and high perceived stress levels. Hypotheses Compared to participants in the last stage of change (maintenance), it was hypothesised that participants in the first stage of exercise change (precontemplation) would have:  lower self-efficacy  less concern over the pros of exercise  more concern over the cons of exercise  poorer self-rated health  higher levels of perceived stress  lower levels of internal health locus of control [From Introduction]